Screen Time dan Kualitas Tidur dengan Kadar Hemoglobin pada Remaja Putri - Maghfirah, Nisa; Masfufah Masfufah; Nuristha Febrianti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Iron anemia is the biggest macro nutritional problem in Indonesia, which occurs in toddlers, pregnant women and adolescent girls. Adolescent girls with anemia are at risk of giving birth to LBW babies (<2500 grams), giving birth to premature babies, neonatal infections and death in the baby's mother during delivery. The aim of this study was to analyze the relationship between screen time and sleep quality with hemoglobin levels in adolescent girls. This research method uses quantitative observational research with a cross-sectional design and a sample size of 76 respondents using a purposive sampling technique. The results of this study show that 55 respondents (72.4%) had normal hemoglobin levels and 21 respondents (27.6%) had poor hemoglobin levels. The bad screen time category was 40 respondents (52.6%) and the good one was 36 respondents (47.4%). And the category of poor sleep quality was 57 respondents (75.0%) and good sleep quality was 19 respondents (25%). The results of this study showed that there was no relationship between screen time and sleep quality and hemoglobin levels in young women at SMA Karya Bakti and SMKN 6 Palu.